Analisis perhitungan harga pokok produksi dengan menggunakan metode full costing dan variabel costing untuk menentukan harga jual pada UMKM Kripik Pisang Chelsilo - Wati, Ricky Katuuk; Saerang, David P. E.; Gerungai, Natalia Y. Telly (Manajemen Bisnis dan Keuangan Korporat, 2025)
The increasingly complex and competitive business environment requires micro, small, and medium enterprises (MSMEs) to manage accurate cost information in determining production costs and selling prices. This study aims to analyze the calculation of cost of goods manufactured using full costing and variable costing methods to determine the selling price of Chelsilo Banana Chips MSME. This research employed a quantitative descriptive approach by collecting data directly from the enterprise’s financial records and production activities. The results show that the enterprise’s existing calculation produced a cost of IDR 65,376 per kilogram with a selling price of IDR 80,000 per kilogram. Using the full costing method resulted in IDR 74,820 per kilogram, while the variable costing method resulted in IDR 68,485 per kilogram. Determining the selling price using the mark-up method produced a selling price of IDR 89,784 per kilogram (20% mark-up) under full costing and IDR 82,866 per kilogram (21% mark-up) under variable costing. These findings highlight the importance of accurate cost allocation methods to improve pricing decisions and profitability for MSMEs.